REBRANDING DESAIN KEMASAN AMENITIES VILLA SAN DI UBUD UNTUK MEMPERKUAT IDENTITAS VISUAL DALAM UPAYA MEMBERIKAN PENGALAMAN MENARIK BAGI PENGUNJUNG - Rimbawan, Ari; Wijaya, I Kadek Adi Putra; Suryani, Ni Nyoman Diah (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2024)
Villa amenities packaging design has an important role in creating a positive first impression and a strong memory about the brand for visitors. This article aims to explore strategies and design concepts for villa amenities packaging that can improve the experience of visitors to Villa San Ubud. This research uses observational and qualitative methods by collecting data from related literature, case studies and interviews. The research results show that packaging design must be able to reflect visual identity, aesthetics, sustainability and brand. Important factors in packaging design in creating attractive packaging are color selection, visual elements and brand consistency. This research provides valuable insights for the lodging industry to improve the visitor experience through innovative and attractive amenities packaging designs.